Effectiveness of Health Educational Program upon Nurses’ practices toward Care of Newborns with Neonatal Jaundice - Khudhair, Suad H. (Journal of the Faculty of Medicine Baghdad, 2016)
Background: Effectiveness of health educational program upon nurses’ practices toward care of newborn with neonatal jaundice in neonatal intensive care unit in pediatric teaching hospitals at Baghdad city. Objective: The study aims to apply a health educational program to improve nurse practical skills toward neonatal jaundice and find the relationship between the nurses’ practices and their demographic characteristics. Patients and Method: A Quasi experimental study was carried out in 3 teaching hospitals (Welfare pediatric Teaching Hospital, Central Pediatric Teaching Hospital and Al-Kadhimiyia Teaching Hospital) in Baghdad City from the 12th June 2015 to 28th of December 2015. The sample (30) nurses who are working in the neonatal intensive care unit. The data were collected through using constructed questionnaire which comprises (50) items. The questionnaire used in pre test before conduction of the program and post test 1 immediately after the application of the program, post test and repeated posttest 2 after two months from first post-test 1. The reliability of the questionnaire was determined through a pilot study and validity through a panel of experts. The data were analyzed through the application of descriptive statistic frequency, percentage, and the application of inferential statistical procedures, which include Pearson correlation coefficient and chi-square. Results: The findings of the study indicated that nurses have poor practices in pretest. But post evaluation revealed good level of practices among nurses toward neonatal jaundice in the neonatal intensive care unit. The program reflects effects on nurse’s practices. There were no statistical significant association between nurses’ practices and their demographic characteristics Conclusion: There was no statistical significant association between nurses’ practice and their demographic characteristics. The study demonstrated that there was poor nurses’ practice at NICU toward care of newborn with neonatal jaundice before application program in pretest and good practices in post 1 and posttest 2